Cadeia de custódia dos documentos arquivísticos: perspectivas no processo judicial eletrônico - SILVA, Mayza Caroline Monteiro da (2022)
With the advancement of Information Technologies and the development of new documentary supports, the digital document emerges, which brings new challenges for the management and preservation of documents, due to the dissonance between archival practices in traditional and digital media. Therefore, the use of standards and requirements in the development of computerized management and preservation systems is indispensable to ensure the reliability of digital documents, including: security, authenticity, preservation, and access. In this sense, digital documents cannot be isolated. They must be within a computerized system and a chain of custody, following an approach that manages it systematically manage them efficient by following models, requirements and regulations, with security since the first stages of the document until its final destination. The objective of this work was to identify the existence of a chain of custody related structures in the Electronic Lawsuit Process system, from the investigation of the normative and legal instruments, since there is a considerable increase of documentary mass in digital media. This research is justified by the difficulties of digital preservation and the inherent characteristics of the digital archive document in the absence of a chain of custody. Regarding the universe of research, the investigation of the electronic judicial process system was delimited in analyze the chain of custody of archival documents and a possible reliable digital archival repository. As a sample, this study uses the use of the Electronic Lawsuit Process in the Regional Labor Court systems of the 8th Region. The methods used for the production of this research are based on a methodological triangulation: literature review, exploratory research, and semi-structured interviews, to present a discussion about what the archival theory exposes in relation to the chain of custody, and the reality from the Electronic Lawsuit Process from the Regional Labor Court systems of the 8th Region. As a result of this research, it was possible to identify gaps related to the requirements made available by MoReq-Jus. Thus, the interviews corroborated an exploratory analysis for the view of the absence of an RDC-Arq, constituting a break in the chain of custody. As final considerations, it is expected that this research will contribute as a source of information to assist in digital preservation strategies about the Electronic Lawsuit Process.